The anti-CD6 antibody itolizumab provides clinical benefit without lymphopenia in rheumatoid arthritis patients: results from a 6-month, open-label Phase I clinical trial (2018)
Itolizumab is a humanized anti-CD6 monoclonal antibody (mAb) that has previously shown encouraging results, in terms of safety and positive clinical effects, in a 6-week monotherapy clinical trial conducted in rheumatoid arthritis (RA) patients. The current Phase I study evaluated the safety and clinical response for a longer treatment of 12 itolizumab intravenous doses in subjects with active RA despite previous disease-modifying anti-rheumatic drug (DMARD) therapy. Twenty-one subjects were enrolled into four dosage groups (0·1, 0·2, 0·4 and 0·8 mg/kg). Efficacy end-points including American College of Rheumatology (ACR)20, ACR50 and ACR70 response rates and disease activity score in 28 joints (DAS28) were monitored at baseline and at specific time-points during a 10-week follow-up period. Itolizumab was well tolerated up to the highest tested dose. No related serious adverse events were reported and most adverse events were mild. Remarkably, itolizumab treatment did not produce lymphopenia and, therefore, was not associated with infections. All patients achieved a clinical response (ACR20) at least once during the study. Eleven subjects (55%) achieved at least a 20% improvement in ACR just 1 week after the first itolizumab administration. The clinical response was observed from the beginning of the treatment and was sustained during 24 weeks. The efficacy profile of this 12-week treatment was similar to that of the previous study (6-week treatment). These results reinforce the safety profile of itolizumab and provide further evidence on the clinical benefit from the use of this anti-CD6 mAb in RA patients. © 2017 British Society for Immunology